Differentiating Ischemic Optic Neuropathy from Glaucoma Using Diagnostic Tests - Smeets, Frédéric; Margot, Astrid; Barbosa-Breda, João; Stalmans, Ingeborg; Lemmens, Sophie (Ophthalmic research, 2024)
Abstract Introduction: Anterior ischemic optic neuropathy (AION) can mimic glaucoma and consequently cause difficulties in differential diagnosis. The purpose of this paper was to summarize differences in diagnostic tests that can help perform a correct diagnosis. Methods: The search strategy was performed according to the PRISMA 2009 guidelines, and four databases were used: MEDLINE, Embase, Web of Science, and Cochrane. Totally, 772 references were eligible; 39 were included after screening with respect to inclusion criteria that included English language and published in the 20 years before search date. Results: Ninety percent (n = 35) of included studies used optical coherence tomography (OCT). Glaucomatous eyes had a significantly greater cup area, volume and depth, cup-to-disk ratio, a lower rim volume and area, and a thinner Bruch’s membrane opening-minimum rim width. Retinal nerve fiber layer (RNFL) thinning in glaucomatous eyes occurred primarily at the superotemporal, inferotemporal, and inferonasal sectors, while AION eyes demonstrated mostly superonasal thinning. Glaucoma eyes showed greater macular ganglion cell layer thickness, except at the inferotemporal sector. OCT angiography measurements demonstrated a significant decrease in superficial and deep macular vessel density (VD) in glaucoma compared to AION with similar degree of visual field damage; the parapapillary choroidal VD was spared in AION eyes compared to glaucomatous eyes. Conclusion: By use of OCT imaging, optic nerve head parameters seem most informative to distinguish between glaucoma and AION. Although both diseases affect the RNFL thickness, it seems to do so in different sectors. Differences in structure and vascularity of the macula can also help in making the differential diagnosis.